Betulinic Acid Protects against Ischemia/Reperfusion-induced Renal Damage and Inhibits Leukocyte Apoptosis - ERCAN, FERİHA (WILEY, 2010)
The possible protective effect of betulinic acid on renal ischemia/reperfusion (I/R) injury was studied. Wistar Albino rats were unilaterally nephrectomized and subjected to 45 min of renal pedicle occlusion followed by 6 h of reperfusion. Betulinic acid (250 mg/kg, i.p.) or saline was administered at 30 min prior to ischemia and immediately before the reperfusion. Creatinine, blood urea nitrogen (BUN), lactate dehydrogenase (LDH) and TNF-alpha as well as the oxidative burst of neutrophil and leukocyte apoptosis were assayed in blood samples. Malondialdehyde (MDA), glutathione (GSH) levels, Na+, K+-ATPase and myeloperoxidase (MPO) activities were determined in kidney tissue which was also analysed microscopically. I/R caused significant increases in blood creatinine, BUN, LDH and TNF-alpha. In the kidney samples of the I/R group, MDA levels and MPO activity were increased significantly, however, GSH levels and Na+, K+-ATPase activity were decreased. Betulinic acid ameliorated the oxidative burst response to both formyl-methionyl-leucyl-phenylalanine (fMLP) and phorbol 12-myristate 13-acetate (PMA) stimuli, normalized the apoptotic response and most of the biochemical indices as well as histopathological alterations induced by I/R. In conclusion, these data suggest that betulinic acid attenuates I/R-induced oxidant responses, improved microscopic damage and renal function by regulating apoptotic function of leukocytes and inhibiting neutrophil infiltration. Copyright (C) 2009 John Wiley & Sons, Ltd.
Keywords: betulinic acid; ischemia/reperfusion; kidney; apoptosis; lipid peroxidation; ISCHEMIA-REPERFUSION INJURY; RAT-KIDNEY; TISSUE-INJURY; FREE-RADICALS; FAILURE; MYELOPEROXIDASE; TRITERPENOIDS; MECHANISMS; DISCOVERY